2015
DOI: 10.1016/j.toxrep.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial toxicity of triclosan on mammalian cells

Abstract: HighlightsWe show (sub)cellular toxicity of triclosan (TCS) on six types of mammalian cells.1–5 μg ml−1 TCS induced metabolic acidification and uncoupled respiration.TCS ceased progressive boar sperm motility at 1 μg ml−1.TCS uncouples ATP synthetase complex V in mitochondrion.TCS caused regression of pancreatic islets to pycnotic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 87 publications
(116 reference statements)
2
51
0
1
Order By: Relevance
“…This topic was recently reviewed by Ruszkiewicz et al (2017). Briefly, TCS was found to affect mitochondrial function (Weatherly et al 2016; Shim et al 2016; Newton et al 2005; Ajao et al 2015), disrupt proper calcium signaling (Cherednichenko et al 2012), alter zinc homeostasis (Tamura et al 2012), and affect immunological parameters (Anderson et al 2013; Yueh et al 2014; Udoji et al 2010; Weatherly et al 2013). …”
Section: Triclosan-mediated Adverse Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This topic was recently reviewed by Ruszkiewicz et al (2017). Briefly, TCS was found to affect mitochondrial function (Weatherly et al 2016; Shim et al 2016; Newton et al 2005; Ajao et al 2015), disrupt proper calcium signaling (Cherednichenko et al 2012), alter zinc homeostasis (Tamura et al 2012), and affect immunological parameters (Anderson et al 2013; Yueh et al 2014; Udoji et al 2010; Weatherly et al 2013). …”
Section: Triclosan-mediated Adverse Health Effectsmentioning
confidence: 99%
“…As previously indicated, several studies showed that TCS exhibited endocrine disrupting effects, which may account for a portion of the adverse reproductive outcomes observed in the epidemiological studies. Mitochondrial disruption by antimicrobial (Weatherly et al 2016; Ajao et al 2015; Newton et al 2005) may also contribute to adverse reproductive effects as proper mitochondrial function is required for embryonic development (Chen et al 2003). …”
Section: Triclosan-mediated Adverse Health Effectsmentioning
confidence: 99%
“…Thus while membrane proteins account for only ~ 30% of the human proteome [9, 10], they play an outsized role in controlling biological processes by regulating the transit of matter and information across the membrane. Indeed, dysregulation of membrane crossing events can have profound effects leading to disease [11, 12] or even death [13, 14]. …”
Section: Membrane Activity Is a Critical Factor In The Biology Of Smamentioning
confidence: 99%
“…Its toxic nature has been proved in several studies conducted on water organisms and also on human cells [9]. The EC50 value of TCS calculated using the Microtox ® test received 0.08 mg/L.…”
Section: Resultsmentioning
confidence: 97%